Keberadaan Esherichia Coli Pada Berbagai Jenis Air - Puji Natalia Kristiani Sitorus; Aina Azzahra; Dimas Ramadhan Lubis; Karen Zefanya Gulo; Puan Adila; Tri Amanda Siregar (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2024)
Water is a very important need for living creatures on earth. Humans, animals, plants and other living creatures need water, clean water is very much needed and is a source of life for living creatures. However, bacteria or germs that cannot be seen by the eye are still detected in the water. The bacteria that are mostly detected in water are; Escherichia coli bacteria. Escherichia coli forms colonies that are convex, smooth with distinct edges, and round. Method used The qualitative literature review research method is an approach used to collect, evaluate, and synthesize studies in the scientific literature that are relevant to a particular topic. Based on research results, Escherichia coli bacteria are found in various types of water such as refillable drinking water, well water and river water as well as swimming pool water